Intensifying heat using MOF-isolated graphene for solar-driven seawater desalination at 98% solar-to-thermal efficiency - Han, Xuemei (2022)
Photothermal materials are crucial for diverse heating applications, but it remains challenging to achieve high energy conversion efficiency due to the difficulty to concurrently improve light absorbance and suppress heat loss. Herein, a zeolitic imidazolate framework-isolated graphene (G@ZIF) nanohybrid is demonstrated that utilizes ultrathin, heat-insulating ZIF layers, and G@ZIF interfacial nanocavity to synergistically intensify light absorbance and heat localization. Under artificial sunlight illumination (≈1 kW m−2), the G@ZIF film attains a maximum temperature of 120 °C in an open environment with a 98% solar-to-thermal conversion efficiency. Importantly, the porous ZIF layer allows small molecules/media to enter and access the embedded hot graphene surface for targeted heat transfer in practical applications. As a proof-of-concept, the G@ZIF-based steam generator realizes 96% energy conversion from light to vapor with near-perfect desalination and water purification efficiencies (>99.9%). This design is generic and can be extended to other photothermal systems for advanced solar-thermal applications, including catalysis, water treatments, sterilization, and mechanical actuation.